Positive Psychological Resources of Orphan students and their peers non-orphans in Liberated Areas - Mohammed, Aseel Sabbar (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the current study is to know the level of positive psychological resources among the sample members and to identify the significance of the differences according to (orphan - non-orphan), in order to achieve the goals of the current research, the researcher prepared the research tool which is positive psychological resource measures, as it consisted of four areas and (34) paragraphs. After confirming all the psychometric properties of the two measures, it was applied to a sample of (200) orphans in the city of Fallujah for the academic year (2019-2020). The results resulted in: Keywords: Positive Psychological Resources, Orphan Students, Liberated Areas • The level of positive psychological resources is • No differences were observed between the two statistical